Better Governance Across the Board Creating Value Through Reputation, People, and Processes - Zinkin, John (Walter de Gruyter, 2019)
Better Governance Across the Board is a practical guide for achieving good corporate governance of organizations regardless of whether they are for profit, listed, state-owned, family owned, or widely held. It delves into the questions boards must ask if they are to fulfill their fiduciary duties, taking account of regulatory issues. Part 1 defines corporate governance, explaining the four reasons why it matters and how it applies to a wide range of organizations. Part 2 explores the "Five P" framework of Purpose, Principles, Power, People, and Processes that helps boards to create sustainable value. Part 3 concludes by showing how the organization's long-term "license to operate" is achieved by boards focusing on the three most important assets of the organization: its reputation; its people, and its processes. This book explores the dilemmas that currently exist in modern approaches to corporate governance and suggests ways of overcoming them. Based on ten years of teaching more than 1,500 directors of publicly listed companies, it integrates key principles of leadership, ethics, branding, and governance into a unique five-factor framework to help directors make good decisions in strategy, risk management, succession planning, internal controls, and stakeholder engagement.